Behind the Curtain: Syria's 1979 Mediation in the Yemen Dispute. Issue 1 (14th January 2020) - Lee, Su‐Mi
Abstract : The literature on international mediation emphasizes the crucial role that mediator impartiality and interest play in a mediation's success. Building on this literature and focusing on the case of Syria's role in resolving the Yemen dispute, my research seeks to demonstrate how a mediator's relationship with an external actor can change the level of the mediator's impartiality and interest and, ultimately, the mediation outcome. Syria's first attempt in 1979 to resolve the Yemen dispute through mediation failed, but its second attempt in the same year was successful. This article describes how Syria's relations with the Soviet Union changed the level of Syria's interest and impartiality toward the dispute between North Yemen and South Yemen. It also explores how and why the Soviets clandestinely helped Syria to become an effective mediator for the dispute. Drawing upon the lessons of this case, I discuss how external factors other than a mediator's bilateral relations with the parties can increase the mediator's impartiality and interest in a dispute.